Poor Healthcare Delivery amidst Petroleum Wealth: The Pathetic Situation of Oil-Bearing Communities in Imo State, Nigeria - Opara, Ikechukwu Jonathan, Ph.D; Eteng, Felix .O, Ph.D; Ezikeudu, Chukwudi .C, Ph.D; Chimaobi Okorie, Ph.D; DR. Uzomba, Chigozie Ikechukwu; AGBOR, Uno I. Ph.D; OWAN, Emeka J. Ph.D (RES MILITARIS, 2023)
It is quite paradoxical and disheartening that a naturally endowed group of communities were pushed into penury amidst abundant wealth. This study examined the contribution of petroleum wealth towards healthcare delivery in Imo State oil-bearing communities. The study adopted mixed research design. The study anchored on Richard Auty’s natural resource curse theory. The population of the study was one hundred thousand and the study adopted five thousand sample size. Ballot method which is a technique of simple random sampling was utilized to determine the communities that were selected for this study. Survey research technique and documentary method were utilized for data collection. Descriptive statistics, Pearson correlation analysis, regression analysis and analysis of variance were utilized for data interpretation. The study discovered that petroleum wealth has not contributed significantly towards healthcare delivery in Imo State oil-bearing communities. The study recommended that Government agencies established for the purpose of ensuring the welfare and development of oil bearing communities (Niger Delta Development Commission and Imo State Oil Producing Areas Development Commission) and multinational oil companies should urgently devote adequate resources towards healthcare delivery in the study area, so as to ameliorate their sufferings.